The Left-handed Plastic Surgery Trainee: Perspectives and Recommendations. Issue 5 (May 2020) - Savetsky, Ira L.; Cammarata, Michael J.; Kantar, Rami S.; Diaz-Siso, J. Rodrigo; Avashia, Yash J.; Rohrich, Rod J.; Saadeh, Pierre B.
Abstract : Background: Left-handed surgeons experience difficulty with tools designed for use in the right hand. The purpose of this study was to examine instrument laterality and to survey the experiences of left-handed plastic surgery trainees. Methods: Count sheets for plastic surgery trays (reconstructive, microsurgery, rhinoplasty, craniofacial) were acquired from Tisch Hospital, NYU Langone Health. Instruments with right-handed laterality were tallied. A survey was also distributed to plastic surgery residents and fellows to determine hand preference for surgical tasks, and those who identified as left-handed described how handedness impacted their training. Results: Right-handed laterality was seen in 15 (31.3%) of the 48 reconstructive instruments, 17 (22.7%) of the 75 rhinoplasty instruments, and 22 (31.0%) of the 71 craniofacial instruments. One-hundred percent of the 25 microsurgery instruments were ambidextrous. There were 97 survey responses. Trainees (17.5%) were identified as left-handed and were more likely than right-handed trainees to report operating with both hands equally or with the opposite hand (47.1% versus 1.3%; P < 0.001). Left-handed trainees were significantly more likely than right-handed trainees to use their nondominant hand with scissors ( P < 0.001), electrocautery ( P = 0.03), and needle drivers ( P < 0.001) and when performing tissue dissection ( P < 0.001) and microsurgery ( P = 0.008). There was no difference in use of the nondominant hand between right and left-handed trainees for knot tying ( P = 0.83) and in use of the scalpel ( P = 0.41). Conclusions: Left-handed plastic surgery trainees frequently encounter instruments designed for the nondominant hand, with which they adaptively perform several surgical tasks. Mentoring may help trainees overcome the laterality-related challenges of residency.